Estimating China's "Equilibrium" Real Exchange Rate - Li, Xiangming (IMF Working Papers; Working Paper, 2005)
The number of studies attempting to estimate the "equilibrium" real value of China's currency has proliferated in recent years as the country's presence in world markets has grown. These studies have sought to establish whether or not a significant part of China's competitive prowess can be attributed to the foreign exchange value of the renminbi. Unfortunately, no consensus has emerged because the studies yield a very wide range of estimates. The paper looks at a sample of these studies, with estimates of undervaluation ranging from zero to nearly 50 percent. It attributes the wide variation in these estimates to the influence of such factors as the different methodologies used, explanatory variables included, subjective judgments of the various researchers in deriving their results, and instability in underlying economic relationships, especially in a rapidly developing economy like China.